Emerging Technologies for Invasive Insects: The Role of Engagement. (16th March 2020) - Kokotovich, Adam E; Delborne, Jason A; Elsensohn, Johanna; Burrack, Hannah
Abstract: Emerging technologies have the potential to offer new applications for managing invasive insects. While scientific and technological advancements are vital to realizing this potential, the successful development and use of these applications will also largely depend on community and stakeholder engagement. To contribute to a relevant and rigorous envisioning of engagement for emerging technologies for invasive insects (ETII), we begin by reviewing key insights on engagement from three scholarly fields: invasive species management, responsible research and innovation, and ecological risk assessment. Across these fields we glean best practices for engagement for ETII: 1) pursue engagement across decision phases and sectors; 2) select context-appropriate participants and methods; and 3) recognize and navigate engagement-related tensions. We illustrate these best practices by describing an ongoing project that uses engagement to inform risk assessment and broader decision making on biotechnologies being developed to address the Spotted-wing Drosophila ( Drosophila suzukii ) invasive fruit fly. We describe completed and planned engagement activities designed to identify and prioritize potential adverse effects, benefits, management actions, and research actions of the proposed genetically engineered sterile male, gene drive, and RNAi biotechnologies. In the face of broadening calls for engagement on emerging technologies, this article provides theoretical and empirical insights that can guide future engagement for ETII.